(untitled) (Bangladesh Journal of Microbiology, 2021)
The emergence of antibiotic-resistant bacteria is a major public health problem. Consequently, the development of new antimicrobials that act on novel bacterial targets and are less susceptible to resistance are of primary importance to researchers in academia and industry alike. The present study was aimed to determine the antimicrobial and antibiofilm activities of Nigella sativa seed extracts. For this, primary (qualitative) and quantitative antibacterial activities of Nigella sativa seed extracts were determined against ten human pathogenic bacteria including four biofilm producing bacterial strains Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae and Staphylococcus aureus. The antibacterial activities as well as minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extracts were evaluated using disc diffusion and macro-broth dilution methods, respectively. The seed extracts of N. sativa exhibited the highest extract yields (w/v) 23.3% and 21.35% with ethanol and petroleum ether, respectively. The crude extract (essential oil) of petroleum ether exhibited superior antibacterial activity (36 mm in diameter zone of inhibition) against biofilm forming E. coli on a disc diffusion assay at a concentration of 1000 μg/disc when compared to that of ethanolic crude extract. Moreover, the lowest MIC and MBC values were determined as 500 μg/ml and 1500 μg/ml respectively with the same petroleum ether extract against E. coli. However, N. sativa essential oil obtained from petroleum ether extract of seed inhibited 94% biofilm formation of E. coli at 2×MIC concentration. Moreover, at the same concentration (2×MIC), the ethanol extract inhibited 56% biofilm formation of P. aeruginosa. These results consistently revealed that it is possible to isolate novel antimicrobial agents capable of completely eradicating microbial infections including antibiotic resistance. Therefore, bioactive natural products present in plant resources would represent a noteworthy alternative to commercial antibiotics helping treatment of human antibiotic resistant infections. Bangladesh J Microbiol, Volume 38, Number 1, June 2021, pp 7-13